Religion and Politics: The Effect of Religiosity Towards Political Behaviour on Female Moslem Adolescent - Siti Asria (Political Sciences Program Study, 2024)
This study examines how religiosity influences the political behavior of adolescent females. Females usually tend to involve less than men in politics, especially when they are adolescents. However, this study shows a different phenomenon. This method of this research is quantitative, using simple linear regression analysis techniques to see the influence between two or more variables. The population in this study was 156 women students and the sample was 61 students. The sampling technique used in this research is a stratified random sampling technique, that is, the population does not have homogeneous characteristics because the characteristics are various. Data collection techniques in this research used a questionnaire with a Likert scale model. The scale instrument has 29 items and 32 valid items. This instrument has been tested for validity and reliability with a standard of 0.361 and the instrument reliability test uses Cronbach's alpha formula with a significance level of 0.05. Based on the research results, it was found that there is a significant influence of female adolescents on their political behavior and preferences, namely being in a good category with a percentage of 80.26%, which means that the majority of female adolescents have an interest in being involved in the political process, especially in politics that are played by religion of Islam. From this study, it can be concluded that the more religious female students are, the higher involvement they are in political participation.